2015
DOI: 10.1016/j.neuropsychologia.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Roaring lions and chirruping lemurs: How the brain encodes sound objects in space

Abstract: The dual-stream model of auditory processing postulates separate processing streams for sound meaning and for sound location. The present review draws on evidence from human behavioral and activation studies as well as from lesion studies to argue for a position-linked representation of sound objects that is distinct both from the position-independent representation within the ventral/What stream and from the explicit sound localization processing within the dorsal/Where stream.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 122 publications
(162 reference statements)
0
4
0
Order By: Relevance
“…Recent evidence indicates that the combined encoding of sound object identity and location involves a separate, third processing stream, referred to also as the lateral pathway (Clarke and Geiser, 2015). Its initial demonstration relied on repetition priming paradigms; neural populations, which encoded the combined representation, displayed repetition enhancement when an object changed position and repetition suppression when it did not, both in EEG (Bourquin et al, 2013) and in 7T fMRI experiments (Da Costa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence indicates that the combined encoding of sound object identity and location involves a separate, third processing stream, referred to also as the lateral pathway (Clarke and Geiser, 2015). Its initial demonstration relied on repetition priming paradigms; neural populations, which encoded the combined representation, displayed repetition enhancement when an object changed position and repetition suppression when it did not, both in EEG (Bourquin et al, 2013) and in 7T fMRI experiments (Da Costa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Sounds are an important source of information for all mammals (Oertel, Cao, Ison, & Allen, 2017). They are mostly used for locating other animals, especially when visual information is limited (Clarke & Geiser, 2015). For people, sounds are not only a source of spatial information, but also of emotional experiences (Duffy, Waitt, & Harada, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, humans categorize sounds in many different ways, for example separating verbal from non-verbal sounds (even infants can do this, Wild et al, 2017), separating action-related sounds from action-unrelated sounds, or distinguishing vocalization sounds produced by living organisms and man-made items, such as tools (Lewis, Brefczynski, Phinney, Janik, & DeYoe, 2005, see also Crivelli, Rueda, & Balconi, 2018;Schneider, Sundararajan, & Mooney, 2018). Interestingly, when processing action-related sounds, including tool sounds, one can observe neural activity in motorrelevant areas of the human brain (Lewis, Phinney, Brefczynski-Lewis, & DeYoe, 2006;Bourquin, Simonin, & Clarke, 2013;Clarke & Geiser, 2015), and in areas related to recognition and performance of actions (Rizzolatti et al, 1996;D'Ausilio et al, 2009), such as Broca's area (Binkofski & Buccino, 2004;Corballis, 2010). Similar effects have also been observed in nonhuman primates.…”
Section: Introductionmentioning
confidence: 99%
“…Eramudugolla and colleagues have shown that the discrimination of animal cries and musical instruments among distractors benefits from spatial cues when the target sound is short (250 ms) but not long (500 ms) [45]. In contrast to the above quoted studies, which used meaningful sounds as targets, the contribution of spatial cues to the segregation of meaningless, previously unheard sound events is less clear [46,47].…”
Section: Neuroimaging Paradigms To Investigate Location-linked Repres...mentioning
confidence: 99%